(untitled) (Journal of Economic Research & Business Administration, 2016)
One of the most important indicators that characterize the success of the bank’s bad loans are. These include bad loans, or loans, the return of which is unlikely or impossible in time. Today, such loans represent a serious problem for both STB Kazakhstan, and for the economy as a whole. For Kazakhstan, the problem of managing problem loans is extremely topical, as indicators of overdue and doubtful debts for the loan portfolios of domestic banks over the same indicators of banks in developed countries. Therefore, this article discusses the status of problem loans, identifies the main causes of nonperforming loans, as well as analyzes the efforts to reduce the level of problem loans in Kazakhstan.